A robust mobile anchor–based localisation technique for wireless sensor network using smart antenna. (20th March 2014) - Biswas, Rathindra Nath; Mitra, Swarup Kumar; Naskar, Mrinal Kanti
This paper introduces a range–based localisation technique namely row matching algorithm (RMA) for wireless sensor network (WSN). In WSN, all stationary targets are configured to broadcast beacon messages periodically using their IDs towards a mobile anchor node equipped with global positioning system (GPS) receiver and smart antennas. The anchor frequently selects a cluster of targets for localisation having received signal strength (RSS) above a pre–defined threshold value. It estimates precise angle of arrival (AOA) and distance using well–known total least squares–estimation of signal parameters via rotational invariance techniques (TLS–ESPRIT) algorithm and path loss model, respectively. Thus, any target can estimate its location taking only two successive beacon messages containing distance and angle information from two different anchor positions and toggles to sleep mode for energy saving. The simulation results validate the robustness of this scheme both in accuracy and energy efficiency without increasing hardware and computational complexity to the targets.